Social attachment, life satisfaction and SNS continuance: a dual-role perspective. (23rd May 2019) - Wang, Nan; Sun, Yongqiang; Zhan, Liuhan; Shen, Xiao-Liang
As the sustainability of social networking sites (SNS for short) heavily relies on the content generated by users, it is important to understand the factors driving users' continuous participation. Considering that SNS has permeated almost every facet of people's lives, this study proposes to understand SNS continuance from the life-oriented perspective beyond the technology-oriented perspective. Further, due to the social nature of SNS, we propose to understand the antecedents of life satisfaction by considering the dual role of social attachment. It is posited to directly enhance individuals' life satisfaction and negatively influence life satisfaction through the mediating effect of envy. An online survey among WeChat Moments users in China was conducted to validate the proposed research model and hypotheses. The data analysis results based on partial least squares approach confirm all the hypotheses.